2021
DOI: 10.3390/fermentation7010039
|View full text |Cite
|
Sign up to set email alerts
|

Cordyceps cicadae NTTU 868 Mycelium with The Addition of Bioavailable Forms of Magnesium from Deep Ocean Water Prevents the Aβ40 and Streptozotocin-Induced Memory Deficit via Suppressing Alzheimer’s Disease Risk Factors and Increasing Magnesium Uptake of Brain

Abstract: Alzheimer’s disease (AD) is a common neurodegenerative disease characterized by continuous accumulation of β-amyloid (Aβ) in the brain. Deep ocean water (DOW) with rich inorganic salts and minerals was proven to promote fungi growth and metabolism. Cordyceps cicada, a functional food fungus, can produce higher anti-oxidant and anti-inflammatory compounds including adenosine, polysaccharide, and N(6)-(2-Hydroxyethyl) adenosine (HEA). This study used DOW as the culture water of C. cicadae NTTU 868 for producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In AD animal models, feeding magnesium-containing substances can effectively supplement the lack of magnesium ions in the brain, thereby improving the effect of AD [34]. This study shows that the magnesium ions absorbed by A. cinnamomea mycelia during the fermentation process can help to supplement the lack of magnesium in the hippocampus.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In AD animal models, feeding magnesium-containing substances can effectively supplement the lack of magnesium ions in the brain, thereby improving the effect of AD [34]. This study shows that the magnesium ions absorbed by A. cinnamomea mycelia during the fermentation process can help to supplement the lack of magnesium in the hippocampus.…”
Section: Discussionmentioning
confidence: 73%
“…Past studies have confirmed that magnesium ions absorbed by Cordyceps cicadae contribute to the uptake efficiency of magnesium ions in the brain. Adding DOW-cultured Cordyceps cicadae can effectively supplement the magnesium ions needed by the human body and inhibit inflammation, thereby preventing the development of AD [34]. Consequently, this study suggests that the Antrodia cinnamomea mycelium cultured in DOW may also hold potential for improving AD, potentially through the enhanced absorption of magnesium.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Cordyceps cicadae, a fungus that parasitizes Lepidoptera larvae, has been consumed as a functional food and used in traditional Chinese medicine for the treatment of palpitations, chronic renal disease, dizziness, and infantile convulsions [98]. Wu et al (2021) [52] utilized deep ocean water for whole submerged fermentation of Cordyceps cicada NTTU 868 prior to administration in an animal model (male, Sprague Dawley, 6-8 weeks old) of AD (continuous 28-day i.c.v. infusion of 180 µL solution containing 24.299 µg Aβ40 and 0.9 mg streptozotocin).…”
Section: Phytochemicals From Traditional Medicinesmentioning
confidence: 99%
“…Specifically, organic magnesium, which can be effectively absorbed to supplement brain magnesium levels, promoted the expression of magnesium transport proteins in the brain, allowing for increased magnesium ion entry into neurons. Supplementing with magnesium reduced the expression of factors associated with Alzheimer's disease, ultimately improving memory and learning capabilities [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%